2008
DOI: 10.1512/iumj.2008.57.3348
|View full text |Cite
|
Sign up to set email alerts
|

Stability results for convex bodies in geometric tomography

Abstract: Abstract. We consider the question in how far a convex body (non-empty compact convex set) K in n-dimensional space is determined by tomographic measurements (in a broad sense). Usually these measurements are derived from K by geometrical operations like sections, projections and certain averages of those. We restrict to tomographic measurements F (K, ·) that can be written as function on the unit sphere and depend additively on an analytical representation Q(K, ·) of K. The first main result states that F (K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Note that pth powers of support functions are homogeneous of degree p. Moreover, Kiderlen [19] showed that differences of pth powers of support functions are dense in the space of continuous functions on S n−1 . So the last equation immediately implies that L p surface area measures are GL(n) contravariant of degree p.…”
Section: Notation and Preliminariesmentioning
confidence: 99%
“…Note that pth powers of support functions are homogeneous of degree p. Moreover, Kiderlen [19] showed that differences of pth powers of support functions are dense in the space of continuous functions on S n−1 . So the last equation immediately implies that L p surface area measures are GL(n) contravariant of degree p.…”
Section: Notation and Preliminariesmentioning
confidence: 99%
“…This observation, which was kindly pointed out to us by Markus Kiderlen, allows us to obtain a strengthened version of one of his results [23].…”
Section: With This Notationmentioning
confidence: 56%
“…We see that I 1 converges uniformly to the integral term in (23). Our goal is to show that I 2 and I 3 approach zero uniformly and also that the limit of…”
Section: With This Notationmentioning
confidence: 90%
See 2 more Smart Citations